How We Engage Graduating Professional Students in Interprofessional Patient Safety. Issue 4 (28th October 2015) - Stevenson, Eleanor; Chudgar, Saumil M.; Turner, Kathleen; Molloy, Margie; Phillips, Beth; Engle, Deborah L.; Clay, Alison S.
Abstract : Problem: Interprofessional curricula on patient safety do not acknowledge the culture and vulnerabilities of the student experience and often do not engage students. Methods: We describe a patient safety collaboration between graduating nursing and medical students during their Capstone courses that fostered conversations about the similarities and differences in professional school experiences around patient safety. Students wrote reflections about an unanticipated patient outcome. Qualitative content analysis was used to characterize themes within student reflections, and to create audience response system questions to highlight differences in each profession's reflections and to facilitate discussion about those differences during the collaboration. Findings: Medical students identified events in which perceived patient outcomes were worse than events identified by nursing students. Nursing students identified more near‐miss events. Nursing students positively impacted the event and attributed action to the presence of a clinical instructor and personal responsibility for patient care. Medical students described themselves as "only a witness" and attributed inaction to hierarchy and concern about grades. Conclusions: Students felt the session would change their future attitudes and behaviors. Stevenson Chudgar Molloy Phillips Engle Clay